PENENTUAN TIPE ALTERASI BERDASARKAN ANALISIS PETROGRAFI, MINERAGRAFI, DAN GEOKIMIA PADA DAERAH KASIMBAR, KABUPATEN PARIGI MOUTONG, PROVINSI SULAWESI TENGAH - Ainul Fatayatis Salamah; Yoga Aribowo; Dian Agus Widiarso; Rinal Khaidar Ali (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Hydrothermal alteration is a complex process, because it involves a change in mineralogy, chemistry and texture resulting from the interaction of hydrothermal solutions with rocks in its path on certain physico-chemical conditions (Pirajno, 1992). Hydrothermal processes in certain circumstances will result a collection of certain minerals known as the set of mineral or mineral assemblage (Guilbert and Park, 1986). One evidence of hydrothermal alteration is the appearance of veins that had level of metal minerals and it is also a change on the rock side, as found in Kasimbar District, Moutong Parigi Regency, Central Sulawesi province. In the area discovered the existence of gold in the alluvium sediments that are the result of weathering schist and quartz veining. Gold is found in alluvium sediments are secondary gold or placer gold. From the research that has been done, found gold in quartz veins trapped on phyllite rocks. This study was conducted to determine the lithology of the region, the study based on petrographic analysis, knowing the characteristics of the rock alteration found in the study area based on petrographic analysis mineragraphy, knowing the type of alteration that develops in the area of research, knowing mineralization contained in the study area. Research in Kasimbar District, Parigi Moutong Regency, Central Sulawesi Province was conducted by analyzing rock samples taken from the area. Analysis is conducted with the petrographic analysis, mineragraphy, lithology and geochemistry of the units located in the area.Based on the results of petrographic thin section analysis of rock samples, lithology contained in Kasimbar District, Parigi Moutong Regency, Central Sulawesi Province is phyllite, granite and gneiss. Alteration characteristics of the study area is known of the characteristics quartz veins, alteration minerals characteristics and metal minerals characteristics. Quartz veins in the study area was divided into two, namely quartz veins in granite and quartz veins in metamorphic rocks (parallel and cut foliation). Characteristic alteration minerals contained in the study area is chlorite, sericite, biotite, epidote and quartz. Mineralization characteristics of the region, is study of sulphide minerals such as pyrite, bornite, and enargite; iron oxide minerals such as magnetite and hematite and the mineral element in the form of native gold (Au). Type of alteration is developed in the research area of prophylitic alteration, potassic alteration, silicification alteration, and carbonization alteration. Type of mineral deposits research areas is high sulfidation epithermal deposits.